Blue bioeconomy localities at the margins: Reconnecting Norwegian seaweed farming and Finnish small-scale lake fisheries with blue policies. (November 2020) - Albrecht, Moritz; Lukkarinen, Jani
The blue bioeconomy is gaining momentum in EU policy debate and various national government strategies as a pathway towards a more sustainable society. Linked to the circularity of economic processes, it combines the promise of (regional) economic development with a sustainable, bio-based transition focused on increased and novel utilisation of aquatic resources. Nonetheless, portrayed as a holistic approach, the political visions of blue bioeconomy reside predominantly in marine environments with little integration of freshwater perspectives or alternative development paths. Rooted in concepts of policy mobility, assembling processes and the positionalities of involved entities, this paper displays two regionally embedded blue bioeconomy developments – Norwegian coastal seaweed farming and Finnish lake fisheries – and their spatially diverse reconnections with national and international policy narratives. By framing a freshwater and a coastal marine case, and their spatial reconnections with an overarching yet diversely translated policy realm, the paper taps into the multiple ontologies of water in blue bioeconomy governance and presents initial empirical and methodological steps towards a relational understanding of its governance processes. Based on four key topical reconnections, the article points to a variety of challenging mismatches between policy narratives, local development processes and potentials. It also suggests conceptual and methodological implications of this approach for further research into "blue" resource governance.